Meta-Analysis of Randomized Trials: Efficacy and Safety of Colchicine for Secondary Prevention of Cardiovascular Disease - Elie Akl; Nazanin Sahami; Christopher Labos; Jacques Genest; Ali Zgheib; Nicolo Piazza; Sanjit Jolly (Journal of Interventional Cardiology)
Background. Colchicine has shown potential cardioprotective effects owing to its broad anti-inflammatory properties. We performed a meta-analysis to assess its safety and efficacy in secondary prevention in patients with established coronary artery disease (CAD). Methods. We searched Ovid Healthstar, MEDLINE, and Embase (inception to May 2022) for randomized controlled trials (RCTs) evaluating the cardiovascular effects of colchicine compared with placebo or usual care in patients with CAD. Study-level data on efficacy and safety outcomes were pooled using the Peto method. The primary outcome was the composite of cardiovascular (CV) death, myocardial infarction (MI), or stroke. Results. A total of 8 RCTs were included with a follow-up duration of ≥1 month, comprising a total of 12,151 patients. Compared with placebo or usual care, colchicine was associated with a significant risk reduction in the primary outcome (odds ratio (OR) 0.70, 95% CI 0.60 to 0.83, P<0.0001; I2=52%). Risks of MI (OR 0.75, 95% CI 0.62 to 0.91, P=0.003; I2=33%), stroke (OR 0.47, 95% CI 0.30 to 0.74, P=0.001; I2=0%), and unplanned coronary revascularization (OR 0.67, 95% CI 0.55 to 0.82, P=0.0001; I2=58%) were all reduced in the colchicine group. Rates of CV and all-cause mortality did not differ between the two groups, but there was an increase in noncardiac deaths with colchicine (OR 1.54, 95% CI 1.10 to 2.15, P=0.01; I2=51%). The occurrence of all other adverse events was similar between the two groups, including GI reactions (OR 1.06, 95% CI 0.94 to 1.20, P=0.35; I2=42%) and infections (OR 1.04, 95% CI 0.84 to 1.28, P=0.74; I2=53%). Conclusions. Colchicine therapy may reduce the risk of future cardiovascular events in patients with established CAD; however, there remains a concern about non-CV mortality. Further trials are underway that will shed light on non-CV mortality and colchicine NCT03048825, and NCT02898610.